Concise Review: Stem Cell‐Based Approaches to Red Blood Cell Production for Transfusion. (20th December 2013) - Shah, Siddharth; Huang, Xiaosong; Cheng, Linzhao
Abstract : Blood transfusion is a common procedure in modern medicine, and it is practiced throughout the world; however, many countries report a less than sufficient blood supply. Even in developed countries where the supply is currently adequate, projected demographics predict an insufficient supply as early as 2050. The blood supply is also strained during occasional widespread disasters and crises. Transfusion of blood components such as red blood cells (RBCs), platelets, or neutrophils is increasingly used from the same blood unit for multiple purposes and to reduce alloimmune responses. Even for RBCs and platelets lacking nuclei and many antigenic cell‐surface molecules, alloimmunity could occur, especially in patients with chronic transfusion requirements. Once alloimmunization occurs, such patients require RBCs from donors with a different blood group antigen combination, making it a challenge to find donors after every successive episode of alloimmunization. Alternative blood substitutes such as synthetic oxygen carriers have so far proven unsuccessful. In this review, we focus on current research and technologies that permit RBC production ex vivo from hematopoietic stem cells, pluripotent stem cells, and immortalized erythroid precursors. Abstract : The focus of this review is on current research and technologies that permit red blood cell production ex vivo from hematopoietic stem cells, pluripotent stem cells, and immortalized erythroid precursors to supplement strained blood supplies for transfusion.